(untitled) (Biological Sciences - PJSIR, 2010)
One hundred tuberculous patients were studied during 2004-2005 to determine acetylation phenotype, frequent mutations of NAT2 gene and to compare acetylation phenotype with NAT2 genotype in Tunisian population. Acetylation phenotype was determined by determination of acetylation index. Five mutations of NAT2 gene were evaluated by PCR/RFLP. Results show bimodal distribution of acetylation SA and RA phenotype, 75% and 25% and genotype 56% and 44%, respectively. Ten NAT2 alleles were found, NAT2*4 being the major one. Thirty-two different genotypes were found (9 RA and 23 SA). The major one was NAT2*6 B/NAT2*4. The concordance value was 79%. A good sensibility (98, 2%) of acetylation test for SA detection was found. Thus, acetylation phenotype in SA is predicted with poor error risk.